Dinamika Waktu Imsak pada Jadwal Imsakiyah Ramadan - Moh Yusuf Faizin; Muhammad Himmatur Riza; Muhammad Habibur Rahman (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2021)
The timing of imsak in Indonesia listed in the Imsakiyah Ramadan schedule is very important to be understood and implemented in the community because imsak relates to the time of the start of fasting both fasting in Ramadan and fasting sunnah and to know the time of the start of fajr prayer. The determination of fajr prayer in each region has a different time, this difference is because each region has different astronomical data from latitude to longitude of a place therefore it takes time ihtiyath. The problem that occurs in the community in implementing imsakiyah schedule is not paying attention to the calibration of the clock, the difference in the use of high sun early at dawn and eating or drinking at dawn.